The association between perception of dental esthetic and oral health related quality of life in adolescents in Dammam, Saudi Arabia - Ibrahem Alsuhimi; Abdulrahman Alshouibi; Abdulkareem Alotaibi; Mohammed Alharbi; Ahmed Aldossary; Mohammed nazir; Khalifa Alkhalifa (Elsevier, 2019)
Objective: To access the association of dental esthetic perception with oral health-related quality of life (OHRQoL) among adolescents in Dammam the Eastern province of Saudi Arabia. Material and methods: This cross-sectional study was conducted on intermediate and high school students in Dammam the Eastern region of Saudi Arabia in the form of questionnaire during February-March 2018. The schools were randomly selected using cluster sampling and students in each school were invited to participate in the study. The students with physical or mental disability were excluded from the study. The perception of dental esthetic was measured by the Arabic version of the Orofacial Esthetic Scale (OES-Ar) on a 5-point Likert scale with 'unsatisfactory'(1) to 'excellent'(5). OHRQoL was measured by the validated Arabic version of the Child Oral Health Impact Profile-Short Form (COHIP-SF 19). Pearson correlation test was performed to investigate an association between esthetic perception and OHRQoL. Results: There were 846 (51.6%) female and 792 (48.8%) male students with mean age14.5 ± 1.6 years in the study. The mean score of perception of esthetic of the sample was 31.44 ± 5.09 which indicates a moderate self-perceived esthetics score (range 8-40). The mean score of OHRQoL was 20.21 ± 11.85 which demonstrates a low quality of life among study participants (range 0-76). The study found a statistically significant correlation between the perception of dental esthetics and oral health related quality of life (Pearson correlation coefficient = −0.573, P.